(untitled) (Global Journals of Research in Engineering, 2014)
Composites are becoming increasingly important in the aerospace industry. At least 30-40 per cent of modern airframes are now made of composites, and this percentage is increasing rapidly due to technological advances in the field. The use of composites for primary structures such as fuselages and wings has grown significantly in transport aircraft. Apart from increased strength at lower weights, composites also meet fatigue and damage tolerance, gust alleviation, and low noise foot print requirements. This paper examines the challenges and advantages of using composites in airframe manufacture, as opposed to other alloys. It also looks at the ways and means to ensure that safety and durability are not compromised by the use of composites. The prime objective of this paper is to highlight the use of advanced composite materials in the field of aerospace and to encourage readers to understand and to write papers on such topics.